Malaria parasitaemia among the neonates in Akure Ondo State, Nigeria - Oluwafemi, Rosena Olubanke; Afolabi, Olajide Joseph; Oniya, Mobolanle O. (International Journal of Contemporary Pediatrics, 2025)
Background: Congenital malaria is thought to be a relatively rare condition in which malaria parasite is transmitted from the mother to the baby during pregnancy or at childbirth. This is so either because the babies were not routinely screened or due to difficulty in detecting the relatively scanty parasite in the newborn period. The study set out to document malaria parasitemia among the neonates in Akure, Ondo state. Methods: Febrile babies admitted into the special care baby unit of University of Medical Sciences Teaching Hospital and Mother and Child Hospital, Akure were tested for malaria parasite using microscopy method and confirmed by nested PCR. Data were analysed using excel and SPSS version 25.0 Results: Nineteen percent of the babies were preterm, 81% were full term and the overall prevalence of malaria among them was 74.7% while prevalence of congenital malaria was 92.9% and prevalence of neonatal malaria was 54.1%. Plasmodium falciparum was the most prevalent infecting species (98.3%), first born babies and male children were significantly more infected (p=0.001). Conclusion: Prevalence of malaria was very high in this study. Malaria infection in the neonates can be difficult to diagnose because the clinical features are nonspecific and parasitaemia often scanty. Screening for malaria parasite should therefore be done as part of routing tests for the neonates.